Control of surface plasmon-polaritons at interfaces between triple quantum dots and nanocomposites. (8th October 2020) - Rahman, Habibur; Ahmad, Iftikhar; Ud Din, Rafi; Ge, Guo-Qin; Ali, Hazrat
Abstract: Surface plasmon-polariton (SPPs) at the interface between a nanocomposite material and a medium, in which triple quantum dots (QDs) are uniformely embedded, are theoretically investigated. The absorption and dispersion spectra of SPPs are shown to have interesting behavior in the proposed system. The plasmonic spectra can be efficiently controlled via gate voltages applied in the triple QD as well as the filling ratio of nanoparticles in the composite. Moreover, the effect of incident frequencies on different features of the propagating plasmons is also manipulated. The propagation length and plasmonic depth are measured with different spectroscopic parameters. This study provides more degrees of freedom for generation and control of SPPs in plasmonic geometries containing QDs or nanocomposites or both. The results may find significant applications in atomic spectroscopy, nano-photonics, photovoltaic devices, biosensors and plasmonster technology.